Interrelationship Between Kidney Function and Percutaneous Mitral Valve Interventions: A Comprehensive Review - Lo, Kevin Bryan (Curr Cardiol Rev, 2019)
Percutaneous mitral valve repair is emerging as a reasonable alternative especially in those with an unfavorable surgical risk profile in the repair of mitral regurgitation. At this time, our understanding of the effects of underlying renal dysfunction on outcomes with percutaneous mitral valve repair and the effects of this procedure itself on renal function is evolving, as more data emerges in this field. The current evidence suggests that the correction of mitral regurgitation via percutaneous mitral valve repair is associated with some degree of improvement in cardiac function, hemodynamics and renal function. The improvement in renal function was more significant for those with greater renal dysfunction at baseline. The presence of Chronic Kidney Disease (CKD) in turn has been associated with poor long-term outcomes including increased mortality and hospitalization among patients who undergo percutaneous mitral valve repair. This was true regardless of the degree of improvement in GFR post repair advanced CKD. The adverse impact of CKD on long-term outcomes was consistent across all studies and was more prominent in those with GFR<30 mL/min/1.73 m(2). It is clear that from these contrasting evidences of improved renal function post mitral valve repair but poor long-term outcomes including increased mortality in patients with CKD, that proper patient selection for percutaneous mitral valve repair is key. There is a need to have better-standardized criteria for patients who should qualify to have percutaneous mitral valve replacement with Mitraclip. In this new era of percutaneous mitral valve repair, much work needs to be done to optimize long-term patient outcomes.